Iowa field reports data, fall 1999 - Iowa State University. Special Collections and University Archives (curator) (2000)
A list of birds sighted dated January 3, 2000. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed